Harnessing Dynamic Electrostatic Fields for Energy Generation with Diode Cells - Renyun Zhang; Magnus Hummelgård; Ye Xu; Martin Olsen; Jonas Örtegren; Göran Thungström; Henrik Andersson; Zhong Lin Wang (Advanced Science, 2025)
Abstract Harvesting energy from distributed mechanical motions has garnered significance in future power sources for small electronics and sensors. Although technologies like triboelectric nanogenerators have shown promising results, their efficacy hinges on the alignment of motion vectors and device architectures. Here, an approach employing stationary diode cells (DiCes) to generate electricity is presented. This approach leverages dynamically changing electrostatic fields to induce potential differences across diode junctions via electrostatic induction, which is verified theoretically and experimentally. DiCes constructed with multiple diodes can directly output DC voltage and current. A 0.02 m2 sized DiCe contains 360 diodes can supply a DC voltage and current of maximum 490 V and 1.08 mA, respectively, which equals a DC power density of 26.5 W·m−2. Capable of functioning in both contact and non‐contact modes, DiCes offer versatile applications, from wirelessly powering implanted medical devices to harvesting energy from vehicles and roads.